Generic and subject-specific professional learning communities in Natural Science - Marimandi, Dhevan (My University, 2022)
This study explored the extent to which the learning from generic professional learning communities (GPLCs) and subject specific learning communities (SSPLCs) worked together or in isolation from one another to offer professional learning opportunities to teachers in the form of developing pedagogic content knowledge (PCK) that might support instructional change in science classrooms. The study was informed by Lave and Wenger’s theory of situated learning and Dewey’s notion of teacher reflection. The research positions teacher learning as being influenced and developed from the relationships that exist between an individual’s own actions in relation to those of others within a context. The data was collected over a period of seven months and was in the form of interviews from three Grade 4 teachers, lesson observations and observations of these teachers participating in SSPLCs and GPLCs in one school in Johannesburg. The findings indicate that these two professional learning communities (PLCs) offer the opportunity for teachers to develop generic knowledge (GK) in the GPLC and PCK in the SSPLC. Working together, these two PLCs offer a context for teachers to develop their PCK. The findings further indicate that the PLCs expose the participants to different artefacts and tools which they use to reflect on their practices and promote learning. By engaging with artefacts, the GPLC provides its participants with knowledge of the language of learning to promote discussions in the SSPLC, were discussions around best practices support teacher reflection.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022